Model Analisis Jalur (Path Analysis): Penelitian Teologi Terapan Kausalitas Kuantitatif - Martinus Duryadi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
The method used in this paper, when viewed from the nature of exploration is applied research, from the nature of explanation is non-causality research, and the method used is qualitative method. The purpose of this paper is to introduce a path analysis research model. Path analysis research is widely used in social sciences such as business economics, management sciences and also in general education sciences. By introducing this type of path analysis research model, the authors hope, this model can be used by students and lecturers in Christian higher education. The path analysis research model includes applied research, where the relationship between causality variables and quantitative data processing and collection methods. The path analysis research model can answer the direct influence or indirect influence of exogenous variables on endogenous variables; In contrast to regression models that only answer the direct influence of exogenous variables on endogenous variables. Path analysis research models are classified into: moderation model, mediation model and combined model of mediation moderation (modmed). In the moderation model, in addition to exogenous variables and endogenous variables, there are also moderation variables. In the moderation path analysis model, it is assumed that the moderation variable reinforces the influence of exogenous variables on endogenous variables. While in the mediation model there are exogenous variables, endogenous variables and mediation variables. In the mediation model, the mediating variable is assumed to function to make the influence of exogenous variables on endogenous variables significant. While the combined model (modmed) is a combination of moderation and mediation models.